2014
DOI: 10.1074/jbc.m113.529172
|View full text |Cite
|
Sign up to set email alerts
|

Specificity Protein 1 (Sp1) Maintains Basal Epithelial Expression of the miR-200 Family

Abstract: Background: Epithelial-mesenchymal transition (EMT) is a key process in embryonic development and cancer metastasis. Results: Sp1 activates miR-200 transcription in epithelial cells and prevents EMT. Conclusion: miR-200 family members require Sp1 to drive basal expression and maintain an epithelial state. Significance: Defining the mechanisms controlling the epithelial state has implications for understanding early differentiation and for designing interventions to prevent cancer metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 70 publications
6
54
0
Order By: Relevance
“…Members of the miR-200 family are downregulated during progression and migration of ovarian and breast cancer, as well as in bladder, pancreatic, prostate and esophageal carcinoma. Furthermore, in several of these entities, downregulation of miR-200 is associated with reduced overall survival and poor response to chemotherapy (28)(29)(30)(31)(32)(33)(34)(35). In the present study, we found that HCC patients with low miR-200a expression had significantly worse prognosis than those with high expression of miR-200a.…”
Section: Discussionsupporting
confidence: 54%
“…Members of the miR-200 family are downregulated during progression and migration of ovarian and breast cancer, as well as in bladder, pancreatic, prostate and esophageal carcinoma. Furthermore, in several of these entities, downregulation of miR-200 is associated with reduced overall survival and poor response to chemotherapy (28)(29)(30)(31)(32)(33)(34)(35). In the present study, we found that HCC patients with low miR-200a expression had significantly worse prognosis than those with high expression of miR-200a.…”
Section: Discussionsupporting
confidence: 54%
“…Our findings added additional miRNA targets regulated by JUN and SP1 in response to KRAS activation, which helped to elucidate the mechanism of JUN and SP1 in mediating KRAS functions. Interestingly, SP1 has been reported to activate mir-200 expression only in epithelial cells but not in mesenchymal cell types (55), strongly suggesting that SP1 may cooperate with different cofactors to affect mir-200 expression differently in distinct cellular contexts.…”
Section: Discussionmentioning
confidence: 99%
“…In the kidney the transcriptional regulation by HNF-1␤ appears to be specific to the miR-200b/a/429 cluster as the levels of the miR-200c/141 cluster are unchanged in HNF-1␤ mutant cells or kidneys. The promoters of the human miR-200b/a/429 and miR-200c/141 clusters have been characterized (41,42), and transcription factors that regulate expression have been identified, including Sp1, the p53/p63/p73 family, and c-Myb (43)(44)(45). These transcription factors may contribute to the residual expression of the miR-200 cluster observed in HNF-1␤ mutant cells and kidneys (Fig.…”
Section: Discussionmentioning
confidence: 99%